Analisis Empat Dimensi Kebijakan Izin Usaha Pengelolaan dan Pengusahaan Sarang Burung Walet Di Kota Pekanbaru Provinsi Riau - Rinaldy May; Tri Yuniningsih; Endang Larasati (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2021)
Pekanbaru City Regulation Number 3 of 2007 concerning Business Permits for Management and Exploitation of Swallow's Nests aims to preserve the environmental sustainability of the management and exploitation of swallow's nest. The problems that arise include the very minimal number of business permits that impact the contribution of regional income, noise pollution, air pollution, environmental impacts, and health problems. The purpose of this study is to analyze the management and management of swallow nests in Pekanbaru City. The approach uses descriptive qualitative data techniques that combine interviews, documentation, and observation. From the research, it can be seen that the policy of managing and exploiting swallow's nest has not been effective. Communication with target groups is carried out through socialization, but it is not practical. The quantity of human resources is still limited. The budget for the operation of the swallow's nest business license is still not optimal. Facilities are also still not optimal. Policy policies seen from the commitment of policy implementers tend to be lacking. Coordination in the supervisory process is not carried out consistently. Supporting factors are the assumptions of explicit policy assumptions and realities, authority resources, social and political conditions, and community support. The inhibiting factor is the information that forms policy formulation, apparatus resources, budget, facilities; economic needs; and target group support.